Mechanism of partial oxidation of methane over a nickel-calcium hydroxyapatite catalyst - Jun, Jin Hyuk; Lim, Tae Hoon; Nam, Suk-Woo; Hong, Seong-Ahn; Yoon, Ki June (ELSEVIER SCIENCE BV, 2006)
The mechanism of partial oxidation of methane to synthesis gas over a nickel-calcium hydroxyapatite catalyst was studied by employing pulse experiments for the powder catalyst and by measuring temperature profiles of the activated, washcoated monolith catalyst. The pulse study showed that after the catalyst was partially reduced, carbon deposition occurred to a great extent and CO was predominantly produced over CO2. Temperature profiles of the monolith catalyst showed that the highest temperature difference between the furnace and the monolith became smaller as the furnace temperature increased. We propose that the reaction occurs primarily via the pyrolysis mechanism or direct dissociation of methane. Adsorbed CO (COs) is a common intermediate and it is rapidly desorbed to produce CO(g), especially at high temperature, or converted to CO2(g), especially at low temperature. The observation that the fully reduced catalyst exhibited lower activity suggests that both metallic Ni and partially oxidized nickel are required in order to exhibit high activity and selectivity. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: PHASE CRYSTALLIZATION METHOD; SYNTHESIS GAS; IN-SITU; PHOSPHATE/HYDROXYAPATITE CATALYSTS; SUPPORTED RHODIUM; SYNGAS; CH4; NI; TEMPERATURE; CONVERSION